2018
DOI: 10.1016/j.redox.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of DAF-16/FOXO3A-mediated stress responses accelerates oxidative DNA damage induced aging

Abstract: DNA damage is presumed to be one type of stochastic macromolecular damage that contributes to aging, yet little is known about the precise mechanism by which DNA damage drives aging. Here, we attempt to address this gap in knowledge using DNA repair-deficient C. elegans and mice. ERCC1-XPF is a nuclear endonuclease required for genomic stability and loss of ERCC1 in humans and mice accelerates the incidence of age-related pathologies. Like mice, ercc-1 worms are UV sensitive, shorter lived, display premature f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 76 publications
0
26
0
Order By: Relevance
“…In addition, FOXO3a activity has been shown to reduce the effects of reactive oxygen species (ROS) production in multiple ways. For example, its expression improves the fidelity of DNA damage repair by arresting the cell cycle to allow the repair of damaged DNA (Fluteau et al, 2015;Gurkar et al, 2018;Tran et al, 2002;Tsai et al, 2008). In addition FOXO3a activation results in the repression of a large number of nuclear-encoded genes with mitochondrial function (Ferber et al, 2012), (Ferber et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FOXO3a activity has been shown to reduce the effects of reactive oxygen species (ROS) production in multiple ways. For example, its expression improves the fidelity of DNA damage repair by arresting the cell cycle to allow the repair of damaged DNA (Fluteau et al, 2015;Gurkar et al, 2018;Tran et al, 2002;Tsai et al, 2008). In addition FOXO3a activation results in the repression of a large number of nuclear-encoded genes with mitochondrial function (Ferber et al, 2012), (Ferber et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study carried out in C. elegans showed that in younger worms, transcription factor cep 1, CEP-1 promotes nuclear DAF-16 activation to induce protective stress response to DNA damage, while CEP-1/p53-dependent loss of DAF-16 nuclear retention was observed upon chronic genotoxic stress in older worms. This change in DAF-16 subcellular localization suggests a potential extra-nuclear role for DAF-16 in chronic genotoxic stress resistance [151].…”
Section: Role Of Mitochondrial Foxo3a In Cellular Stress Responsementioning
confidence: 99%
“…Forkhead box O 3a (FOXO3a) is a key transcriptional regulator of proteins that regulates a wide spectrum of biological processes, including proliferation (4), cell cycle regulation (5), survival (6), apoptosis (7), and autophagy (8). FOXO3a is also associated with oxidative stress (9), DNA damage (10), and longevity (11). FOXO3a is a key downstream transcription factor of the PI3K/AKT pathway.…”
Section: Introductionmentioning
confidence: 99%